ANALISIS KEMAMPUAN VO2MAX PADA MAHASISWA BARU ILMU KEOLAHRAGAAN UNIVERSITAS PGRI MADIUN 2024 - Pramana Putra, Saddan; Ambri Damanik, Saipul; Atesya Kesumawati, Selvi (JURNAL ILMU KEOLAHRAGAAN, 2024)
The level of physical fitness, particularly VO2max, plays a crucial role for sports science students in enhancing athletic performance, health, and injury prevention. This study aims to analyze and evaluate the VO2max capability levels of new students in the Sports Science Program at Universitas PGRI Madiun for the 2024 cohort. It also explores methodologies for measuring VO2max, including the Multi-stage Fitness Test (MFT). The findings aim to equip new students with the necessary knowledge to apply this understanding in their future careers.The study employed a quantitative descriptive method, collecting data using the Multi-stage Fitness Test (MFT). Results revealed that 75% of students fell into the "very poor" and "poor" categories for VO2max levels. Factors such as gender, age, sports background, genetics, and environment were found to influence VO2max variations. These findings underscore the need for fitness improvement programs through regular exercise and healthy lifestyle practices to support students' physical health, aerobic capacity, and academic success